Exploring Metacognitive Strategies to Support Young Learners in Developing Their Learner Autonomy - Suharto, Pipit Prihartanti; Damayanti, Ika Lestari; Lengkanawati, Nenden Sri (International Journal of Language Education, 2025)
This study investigates the role of metacognitive strategy instruction in fostering learner autonomy among young EFL learners. Employing participatory action research, it involved a primary school English teacher and 18 fourth-grade students in an instructional intervention structured around the 'Plan Do Review' reflective framework. Data were collected primarily through classroom observations. Findings indicate that explicit instruction incorporating goal-setting, multimodal scaffolding, and structured reflection enhanced learners’ metacognitive awareness and promoted greater learner autonomy. These positive outcomes were largely attributed to the systematic, scaffolded approach of the intervention, which enabled students to develop metacognitive skills gradually while receiving ongoing support and feedback. Practical implications include recommendations for integrating structured reflection in EFL classrooms and emphasizing differentiated, adaptive teacher training to accommodate learners' varied cognitive readiness and familiarity with reflection.